Investigation of the effect of Interleukin-1 receptor antagonist (IL-1ra) on markers of inflammation in non-ST elevation acute coronary syndromes (The MRC-ILA-HEART Study) - Flather Marcus D; Lucking Andrew J; Fox Keith AA; Hall Alistair S; Greenwood John P; Gunn Julian P; Morton Allison C; Crossman David C; Lees Belinda; Foley Claire E (Trials, 2008)
Abstract Background Acute Coronary Syndromes account for 15% of deaths in the UK, and patients remain at significant risk of re-admission for future complications and death. Pathologically the underlying process of atherosclerosis is driven by inflammatory mechanisms, which are activated in ACS patients. Previous studies have investigated the role of inflammatory markers in this process, including interleukin 1 (IL-1) and C Reactive Protein (CRP). Pre-clinical studies indicate that IL-1 may be a primary driver of ACS and that the naturally occurring interleukin-1 receptor antagonist (IL-1ra) may inhibit the atherosclerotic process. This study will investigate the effects of IL-1ra on inflammatory markers in man. Methods/design Three centres in the UK are planning to recruit 186 Non-ST elevation myocardial infarction patients to receive either interleukin-1 receptor antagonist (Anakinra) or matching placebo. Patients will receive a daily subcutaneous injection of either study drug or placebo over a 14 day period. The primary outcome is area under the curve of high sensitivity C-Reactive Protein (CRP) over the first 7 days. Discussion The MRC-ILA-HEART Study is a proof of concept clinical trial investigating the effects of IL-1ra upon markers of inflammation in patients with Non-ST elevation myocardial infarction. It is hoped this will provide new and exciting information in relation to an "anti-inflammatory" strategy for patients with acute coronary syndrome. Trial registration ISRCTN89369318